The Impact of Subspecialty Fellows on Orthopaedic Resident Surgical Experience: A Multicenter Study of 51, 111 Cases. Issue 6 (15th March 2021) - Jiang, Sam Y.; Carlock, Kurtis D.; Campbell, Sean T.; Vorhies, John S.; Gardner, Michael J.; Leucht, Philipp; Bishop, Julius A.
Abstract : Introduction: Meaningful participation in surgery is important for orthopaedic resident education. This study aimed to quantify the effect of fellows on resident surgical experience. We hypothesized that as fellowship programs expanded, resident caseload would decrease, whereas "double-scrubbed" cases would increase. Methods: This multicenter retrospective study included 9 years of surgical caselog data from two orthopaedic residency programs. Six subspecialty services on which fellow number varied over time were included (trauma, spine, foot and ankle, adult reconstruction, and hand). Case volume and personnel composition per case were extracted. Statistical analysis was performed with two-sample equal variance Student t -tests. Results: A total of 51, 111 cases were assessed. Surgical volume increased across all sites/services over time. Fellow numbers did not affect average resident caseload. However, in years with more fellows, an 11% decrease in one-on-one resident-attending cases ( P = 0.002) and a 17% increase in resident-fellow-attending "double-scrubbed" cases was observed ( P < 0.001). Discussion: Increasing orthopaedic fellows did not affect resident case volume but resulted in fewer one-on-one cases with the attending and more "double-scrubbed" cases with a fellow. The implications of these findings to resident education require further study, but orthopaedic educators should be aware of these findings to try to maximize educational opportunities. Level of Evidence: Level III